Yield stability of the black bean DOR-500 line in the humid tropic from Mexico. - López, Ernesto; Acosta, Jorge A.; Cano, Octavio; Fraire, Guillermo; Cumpián, Javier; Becerra, Enrique Noe; Villar, Bernardo; Ugalde, Francisco (Agronomía Mesoamericana, 2006)
The present study was carried out during 1994 to 1997. Adaptation of the DOR-500 line was evaluated in eight experiments established in the humid tropic of Mexico, five in the state of Veracruz, two in Chiapas and one in Guerrero. The line DOR-500 was excellent according of its yield, wide adaptation and stability (1063/ kg/ha, bi=1.0, S2di= 0). DOR-500 line was established in commercial plots in ten locations of the Mexican Southeast (tropical climate) comparing this line to the regional and local control treatments; it was obtained a yield of 1327 kg/ha. The DOR-500 line was tolerant to the bean golden mosaic virus (BGMV), Leaf spot (Phaseoisariopsis griseola), and rust (Uromyces appendiculatus). The Dor-500 line is being registered as a new variety for the production regions of Mexico.